2014
DOI: 10.1126/science.1251915
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of a heterotetrameric NMDA receptor ion channel

Abstract: N -methyl-D-aspartate (NMDA) receptors belong to the family of ionotropic glutamate receptors, which mediate most excitatory synaptic transmission in mammalian brains. Calcium permeation triggered by activation of NMDA receptors is the pivotal event for initiation of neuronal plasticity. Here we show the crystal structure of the intact heterotetrameric GluN1/GluN2B NMDA receptor ion channel at 4 Å. The NMDA receptors are arranged as a dimer of GluN1-GluN2B heterodimers with the two-fold symmetry axis running t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

26
709
2
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 535 publications
(740 citation statements)
references
References 44 publications
26
709
2
3
Order By: Relevance
“…This conclusion is also consistent with structural data showing that the LBD of GluA2 contains a number of zinc binding sites formed mainly by histidine residues (42). Because the ATD and LBD are tightly packed in NMDARs but more separated in AMPARs, with the consequence that the ATD is not a regulatory site for AMPARs (8,9), we propose that the LBD is a more likely site for allosteric AMPAR modulation by zinc. More studies are needed for determining the subunit sensitivity, the binding site, and the underlying biophysical mechanism of zinc-mediated AMPAR inhibition.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…This conclusion is also consistent with structural data showing that the LBD of GluA2 contains a number of zinc binding sites formed mainly by histidine residues (42). Because the ATD and LBD are tightly packed in NMDARs but more separated in AMPARs, with the consequence that the ATD is not a regulatory site for AMPARs (8,9), we propose that the LBD is a more likely site for allosteric AMPAR modulation by zinc. More studies are needed for determining the subunit sensitivity, the binding site, and the underlying biophysical mechanism of zinc-mediated AMPAR inhibition.…”
Section: Discussionsupporting
confidence: 78%
“…6 and 7]. Recent structural studies revealed that the amino terminal domain (ATD) and ligand-binding domain (LBD) are tightly packed in NMDARs but not AMPARs (8)(9)(10). These structural differences explain some of the functional differences in allosteric modulation between AMPARs and NMDARs, such as why the ATD of NMDARs, unlike that of AMPARs, modulates function and contains numerous binding sites for allosteric regulators.…”
mentioning
confidence: 99%
“…S2). Because the assembly of iGluR heterotetramers is mediated via a dimer of dimers organization (25,26,42) and coexpression of GluRIIA/E and Neto β induced small but significant currents, we speculate that the order of subunit arrangement in the Drosophila NMJ heterotetramers entails the formation of GluRIIA/E and the reciprocal C/D dimers. In Xenopus oocytes, surface expression of iGluR heterotetramers is much lower than that of vertebrate GluK2 (Fig.…”
Section: Discussionmentioning
confidence: 96%
“…3A), a position that in vertebrate GluA2 and GluK2 AMPA and kainate receptors is converted to an arginine by RNA editing (20)(21)(22). In the M3 helix, which forms the entrance to the ion channel pore in glutamate receptors (23)(24)(25)(26), Drosophila GluRIIB has three amino acid substitutions; most notable is the replacement of asparagine by lysine at position 647 (Fig. 3A).…”
Section: Efficient Receptor Expression and Function Requires Multiplementioning
confidence: 99%
“…Recently, two independent studies, by Karakas and Furukawa [4] and Lee et al [5], revealed the first insight of the crystal structure of NMDA receptor in almost complete configurations. In both studies, the NMDA receptors are heterotetrameric complexes comprised of two GluN1 and two GluN2B subunits.…”
Section: Editorialmentioning
confidence: 99%